2002
DOI: 10.1592/phco.22.1.88.33503
|View full text |Cite
|
Sign up to set email alerts
|

Use of Potentially Inappropriate Drugs in Nursing Homes

Abstract: On admission, 33% of residents were receiving at least one potentially inappropriate drug. After 90 days, the drug was discontinued in 16% of these residents. Of those not receiving a potentially inappropriate drug on admission, one was begun in 18%. Demographic factors and number of drugs taken by patients were associated with the use of potentially inappropriate drugs. CONCLUSIONS; Use of potentially inappropriate drugs was prevalent on admission and at 90 days after admission. Discontinuation was highest am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
39
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 30 publications
5
39
1
Order By: Relevance
“…One study found that polypharmacy was associated with a number of specific diseases including congestive heart failure, hypertension, depression, anxiety, and diabetes (Chiang et al, 2000). Others have found less inappropriate medication usage among nursing home residents with dementia than among those without dementia (Dhall et al, 2002;Nygaard et al, 2003;Perri et al, 2005). The objective of the current study is to describe medication prescription patterns for nursing home residents with end-stage dementia and to describe how this pattern changes as subjects approached the time of death.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…One study found that polypharmacy was associated with a number of specific diseases including congestive heart failure, hypertension, depression, anxiety, and diabetes (Chiang et al, 2000). Others have found less inappropriate medication usage among nursing home residents with dementia than among those without dementia (Dhall et al, 2002;Nygaard et al, 2003;Perri et al, 2005). The objective of the current study is to describe medication prescription patterns for nursing home residents with end-stage dementia and to describe how this pattern changes as subjects approached the time of death.…”
Section: Introductionmentioning
confidence: 98%
“…Nursing home residents receive more medications than any other subpopulation (Chutka et al, 1995), and many of these medications may be considered inappropriate (Beers et al, 1992). Polypharmacy is associated with inappropriate medication use, which in turn is associated with the occurrence of adverse events including hospitalization and death (Chiang et al, 2000;Dhall et al, 2002;Lau et al, 2005;Perri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These individuals are prescribed a greater number of medications than those residing in the community [2,3]. Inappropriate prescribing has been reported to be higher among elderly in long-term care, compared to community dwelling elderly, with estimates as high as 33% to 40% [4-6]. Multiple medical illnesses, functional impairment and cognitive deficits contribute to a higher risk of adverse drug reactions in the elderly residing in long-term care [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a high prevalence of inappropriate medication use (12-40%) among the elderly across different healthcare settings. [2][3][4][5][6][7][8][9] Criteria for determining the appropriateness of medication use in the elderly have been developed by Beers et al 2,10 Inclusion in this list of 49 drugs considered inappropriate for the elderly implies that healthcare providers should carefully weigh the efficacy, chronic use, and/or risk versus benefit issues before any of these agents are prescribed in this population. These criteria have been used in several studies in the elderly, which have reported some level of inappropriate prescribing in up to 40% of nursing home patients.…”
mentioning
confidence: 99%